Epidemiological analysis of occupational dermatitis notified in Brazil in the period 2007 to 2012 - Gabriela Yumi Plombom; Mariana Santos de Oliveira; Fernanda Lika Tabushi; Amanda Joekel Kassem; Kátia Sheylla Malta Purim; Renato Mitsunori Nisihara (Sociedade Brasileira de Dermatologia, 2016)
Abstract: BACKGROUND: Occupational dermatitis affects the quality of life and productivity of workers. Studies on the subject are scarce in Brazil. It is estimated that the disease is underreported and that many affected patients do not seek health care. OBJECTIVES: To conduct an epidemiological analysis of occupational dermatitis notified via SINAN in Brazil from January 2007 to December 2012; evaluate the profile of patients assisted; and check the main etiological agents involved. METHODS: We analyzed the compulsory notification forms of cases of occupational dermatitis filled nationwide during January 2007 to December 2012. RESULTS: During the study period 3027 cases of occupational dermatitis were notified in Brazil. In 61.4% of cases patients were men aged between 35-49 years (39.6%). The most described etiological agent was chromium (13.9%). The location of the body most affected was the hands, with 28.4% of cases. The construction sector is implicated in 28.7% of cases and domestic services by 18%. Allergic contact dermatitis is the most prevalent occupational dermatitis (20.6%) and the region with the highest number of notifications was the Midwest, with 376.4 cases per million inhabitants. CONCLUSIONS: The profile of patients most affected by occupational dermatitis in Brazil during the study period was: men with elementary school, aged between 20 and 49 years old and working in the construction industry. The most common occupational dermatitis were allergic contact dermatitis caused by chromium after years of exposure, being the hands and head the parts of the body most affected.